Rendimento e valor nutritivo de grãos de cevada superprecoce no outono em diferentes épocas de semeadura, doses de nitrogênio e espaçamentos - Biazus, Valdéria (2015)
The grain yield of super-early barley in fall season can become an alternative management for the optimization of agricultural areas, producing grain and maintaining coverage on the ground. Barley is an excellent winter option for the agricultural system in southern Brazil, due to its precocity that allows sowing and harvesting before the wheat. Furthermore, the barley grain presents adequate nutritional value and can be an option in the management of food production animals, leading to significant reduction in feed costs, without drop in productive index. The objective of this work was to evaluate the grain yield and nutritive value of the super-early barley BRS Aliensa for animal feed and to identify the specific crop management in the fall. Two experiments were conducted in the Experimental Station of Embrapa Trigo, in Passo Fundo, RS, during the year of 2014, in Dystrophic Red Latosol. In addition, it was possible to verify that the barley genotype BRS Aliensa presented low grain yield, however has adequate nutritional value for use in animal feed.